Medeiros and Albuquerque law: a discursive artifact in its historical context (Ágora Journal, 2026)
This article addresses the issue of copyright in Brazil in the second half of the 19th century, focusing on Law No. 496, of 1 August 1898, popularly referred to as the Medeiros e Albuquerque Law. The research is based on the tools of legal historiography, particularly the premise that law is, above all, a contingent phenomenon; that is, social, political, and cultural conditions directly influence legislative production, which in turn shapes reality. Accordingly, the study seeks to clarify the factors that drove the creation of Law No. 496 of 1898 during Brazil’s monarchical-to-republican transition. Between 1850 and 1898, several personalities participated in the debate on the regulation of copyright, in a process influenced by events such as the abolition of slavery and the rise of progressive bourgeois values. Medeiros e Albuquerque experienced decisive moments for the consolidation of copyright law. His profile and career contributed to his name being associated with the law, reflecting the demands of intellectuals who defended both the cultural value of art and the economic protection of intellectual work.
Keywords: Copyright; Medeiros e Albuquerque; 19th century; Progressive republican ideals; Culture.